Growth performance, productive performance, and visceral characteristics of Japanese quails (Coturnix coturnix japonica) fed with fully defatted black soldier fly larvae - Nacilla, Elaisa Jean B.; Evacitas, Florence C. (Cebu City, Cebu Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
The use of insects, such as the black soldier fly (BSF) has gained momentum as an alternative protein source in poultry nutrition due to high protein and fat, superior amino acid profile, and minerals in their biomass compared to soybean meal. Japanese quails are sensitive to dietary changes, especially during the growing period, a critical time for their growth that will directly influence their laying performance. However, evaluation of the effect of defatted black soldier larvae meal on the quail?s overall growth and productive performance is in its infancy, specifically the suitability of fully defatted BSF larvae (FDBSFL). Thus, this study aims to determine how the inclusion of varying proportions of fully defatted black soldier fly will affect the growth performance, productive performance, and visceral characteristics of Japanese quails. Thirty-six (36) laying quails were randomly assigned to four dietary treatments: Commercial feed (control), 10 % FDBSFL (T1), 20 % FDBSFL (T2), and 30 % FDBSFL (T3). Growth performance, productive performance, and visceral characteristics were not significantly affected by increasing levels of FDBSFL. However, some notable variances were observed. Japanese quails fed with 30 % FDBSFL have higher feed intake, higher feed conversion ratio, and weight gain at age 49-58 days old. Furthermore, quails fed with 30% FDBSFL had delayed egg production, and higher albumen but lower yolk content in their eggs. FDBSFL diets resulted in intense yolk color (bright yellow to pantone) compared to commercial feed diets (pale yellow). Lastly, the relative weight (%) of liver (2.86 g, 2.60 g, 2.22 g) and visceral fat (0.98 g, 1.22 g, 1.41 g) of quails fed with FDBSFL meal were lower than quails fed with commercial diet (2.89 g liver weight, 1.81 g visceral fat). In conclusion, the inclusion of 30% FDBSFL in quails may not significantly affect their growth performance and visceral characteristics but can potentially reduce their egg production performance. Therefore, a fully defatted black soldier fly larvae of up to 20% can be a good alternative protein source during growth and egg laying period of Japanese quails.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu. July 2022